Motivation to exercise in patients with chronic low back pain - Nevelikova, Marketa; Zlamal, Filip; Dosbaba, Filip; Su, Jing Jing; Batalik, Ladislav (BMC musculoskeletal disorders, 2025)
BACKGROUND: Chronic low back pain (CLBP) is one of the most common musculoskeletal problems worldwide. Even though regular exercise is recommended as the primary conservative approach in treating this condition, significant part of patients lead sedentary lifestyle. Motivation to exercise is one of the variables that effects the adherence of exercise-based treatments. This study aimed to characterize the motives for exercise, as posited by self-determination theory, in persons with CLBP, and to identify subgroups (clusters) of motivational profiles in combination with socioeconomic and clinical characteristics using k-means cluster analysis. METHODS: Data were collected between September 2022 and September 2023. A total of 103 adults with CLBP completed the paper-pencil Exercise Self-Regulation Questionnaire (SRQ-E) and provided self-reported measures on anthropometric and socio-economic characteristics. Inclusion criteria were age (≥ 18 years) and non-specific CLBP (lasting longer than 12 weeks). Exclusion criteria included specific lumbar spine pathology (e.g., fracture, cancer), worsening neurological symptoms, recent injection therapy (within 3 months), and current alcohol or drug misuse. RESULTS: Three distinct motivational clusters were identified among the 103 participants: two clusters were characterized by predominantly autonomous motivation (moderately motivated cluster: 31.1%; highly motivated cluster: 54.4%), while one cluster (controlled convinced cluster: 14.6%) showed a higher level of controlled motivation. Associations were observed between the controlled cluster and factors such as higher disability scores, longer duration of pain, greater number of completed physiotherapy sessions, and elevated BMI. Notably, the controlled motivation cluster was linked with poorer clinical outcomes. CONCLUSIONS: This study provides insights into the exercise motivation of patients with CLBP, revealing that while most patients were primarily autonomously motivated, a notable subgroup exhibited lower, controlled motivation. The presence of controlled motivation was associated with worse functioning, longer pain duration, and increased utilization of physiotherapy services. Although these findings suggest a link between motivational profiles and clinical outcomes, the cross-sectional design limits causal inferences. Further research is needed to explore these relationships longitudinally. TRIAL REGISTRATION: ClinicalTrials.Gov Identifier: NCT05512338 (22.8.2022, NCT05512338).
Keywords: dospělí; průzkumy a dotazníky; Female; Self-determination theory; Adult; Physiotherapy adherence; ženské pohlaví; Chronic low back pain; Surveys and Questionnaires; lidé; cvičení; Exercise Therapy; Low Back Pain; Exercise motivation; Male; Aged; lumbalgie; motivace; chronická bolest; terapie cvičením; Chronic Pain; lidé středního věku; senioři; mužské pohlaví; Exercise; Middle Aged; Motivation; Humans